Lecturers’ Opinions and Preferences: Printed Book or E-Book for Science Teaching - Syilvia Wenny J; Yahfenel Evi Fussalam; Rian Dani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Even while printed books and electronic books frequently contain the same material, they differ greatly from one another and each format has its own benefits and drawbacks. This study's purpose is to acquire a thorough grasp of the opinions and preferences of the lecturers in employing book formats for science teaching. The findings of the study would assist other lecturers in thinking through and selecting implementation strategies for employing those two types of book formats. Then, this study identifies the advantages and disadvantages of digital versus print books as well as the reasons why lecturers favor one over the other through this research. This study used a qualitative phenomenological methodology. The stages of the research are selecting research informants, collecting the data and analysis to drawing conclusions. The instrument used in this study is in depth interview. Data collection was carried out through interviews with lecturers who have used both books’ formats. Based on the results of the study it was found that there were 35% lecturers who preferred to use printed books, 10% lecturers who preferred to uses e-books, and 55% lecturers who preferred to use both printed and e-books. They preferences were based on the situational of teaching and learning process.